Preparation and Properties of Cyanobacteria-Based Carbon Quantum Dots/Polyvinyl Alcohol/ Nanocellulose Composite - Xu, Li (Polymers (Basel), 2020)
Blue luminescent carbon quantum dots (CQDs) were prepared from cyanobacteria by a hydrothermal method. The PL quantum yields of the obtained CQDs was 5.30%. Cyanobacteria-based carbon quantum dots/polyvinyl alcohol/nanocellulose composite films were prepared, which could emit bright blue under UV light. FTIR characterization showed that the composite films had hydroxyl groups on the surface and no new groups were formed after combining the three materials. The photoluminescence (PL) spectra revealed that the emission of the prepared CQDs was excitation dependent. Studies on the water resistance performance and light barrier properties of the composite films showed that they possessed higher water resistance properties and better UV/infrared light barrier properties. Therefore, we report the cyanobacteria-based carbon quantum dots/polyvinyl alcohol/nanocellulose composite films have the potential to be applied in flexible packaging materials, anti-fake materials, UV/infrared light barrier materials and so on.